Herbal medicine and non-hospital utilisation in Malaysia during the COVID-19 pandemic - Ashwini Reddy Ravi Chander; Teik Guan Tan; Rahela Zaman; Eugenie Sin Sing Tan; Normina Ahmad Bustami; Chung Keat Tan (Discover Public Health)
Abstract Background COVID-19 is an infectious disease that led to over 3 million deaths globally during the pandemic. Herbal medicine (HM) has become popular during the COVID-19 pandemic; however, it is unclear whether this reliance on HM has affected conventional medical practices, including hospital utilisation. Objective The study’s objective was to examine the usage of HM from January 2021 to December 2021 amidst the COVID-19 pandemic and its association with non-hospital utilisation among Malaysians. Method A cross-sectional study was conducted on the Malaysian population aged 18 years and older. Findings 393 respondents from diverse ethno-religious backgrounds (Malays 26.5%, Chinese 34.1%, Indians 34.6%, Indigenous peoples 3.3% and others 15%) participated in the study, with 59% being females (n = 232). Most respondents (n = 286, 72.8%) reported fear of visiting hospitals during the pandemic. As a result, 51.4% (n = 202) turned to HM as an alternative due to its availability (n = 38, 18.8%) and cost-effectiveness (n = 36, 17.8%). Most consumers (n = 133, 33.8%) preferred HM certified by the Ministry of Health (MOH), Malaysia and purchased them from pharmacy retailers (n = 114, 29%). A significant association (P < 0.05) between HM consumption and non-hospital utilisation was found. Nearly half of the respondents (n = 186, 47.3%) alleviated the severity of their symptoms. Logistic regression revealed that HM users were 1.96 times more likely not to utilise hospital than non-HM user. Conclusion Overall, HM consumption during the pandemic was based on personal knowledge and was significantly associated with non-hospital utilisation. Fear of COVID-19 was one of several contributing factors to this trend.